2016
DOI: 10.1111/padm.12266
|View full text |Cite
|
Sign up to set email alerts
|

Servant Leadership and Follower Job Performance: The Mediating Effect of Public Service Motivation

Abstract: This article advances our understanding of the effects of servant leadership, an employee-and community-focused leadership style, on followers' public service motivation (PSM) and job performance. Based on social learning theory, we argue that by emphasizing to their followers the importance of serving others both inside and outside the organization and by acting as role models by serving others themselves, servant leaders enhance job performance by engendering higher PSM in their followers. A multilevel analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
150
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 150 publications
(172 citation statements)
references
References 61 publications
20
150
0
2
Order By: Relevance
“…Also, the Chinese culture emphasises guanxi and personal favour (Xin & Pearce, ), which could result in high response rate in surveys (Bui, Zeng, & Higgs, ). For example, similar or even higher response rate was reported in other studies conducted in China, such as 83% (Schwarz, Newman, Cooper, & Eva, ), 82% (Miao, Eva, Newman, & Schwarz, ), 93% (Liu, Luksyte, Zhou, Shi, & Wang, ), and 95% (Wang, Xu, Sun, & Liu, ). For these reasons, although the response rate is high, we do not consider it as unduly problematic.…”
Section: Methodssupporting
confidence: 80%
“…Also, the Chinese culture emphasises guanxi and personal favour (Xin & Pearce, ), which could result in high response rate in surveys (Bui, Zeng, & Higgs, ). For example, similar or even higher response rate was reported in other studies conducted in China, such as 83% (Schwarz, Newman, Cooper, & Eva, ), 82% (Miao, Eva, Newman, & Schwarz, ), 93% (Liu, Luksyte, Zhou, Shi, & Wang, ), and 95% (Wang, Xu, Sun, & Liu, ). For these reasons, although the response rate is high, we do not consider it as unduly problematic.…”
Section: Methodssupporting
confidence: 80%
“…As individuals with high levels of PSM and entrepreneurial leaders were found to elicit employees' innovative behavior, hiring practices could assess job candidates' PSM and propensity to engage in entrepreneurial leadership activities. In China, questions about PSM and entrepreneurial leadership could be integrated into the annual civil service examinations, which were taken by 1.4 million entry‐level applicants in 2015 (Schwarz et al 2016). Our results show that public organizations would be well advised to design jobs that civil servants consider meaningful and at which they feel competent.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the definition, public management scholars have shown a continued interest in job performance, seeking to understand the mechanisms that enhance it. Scholars have identified wide-ranging antecedents of job performance such as employee attitudes (for example Potipiroon & Faerman, 2016), workplace policies and procedures (for example Anand et al, 2012), and leadership (for example Schwarz et al, 2016). A meta-analysis by Cerasoli, Nicklin, and Ford (2014) showed that intrinsic motivations are more likely to result in higher-quality performance than extrinsic motivators.…”
Section: Psm and Job Performancementioning
confidence: 99%